Mutu Sensoris Dan Sifat Fisik Nugget Ayam Yang Ditambahkan Tepung Ubi Jalar Ungu (Ipomoea batatas L) - Ratulangi, F.S.; Rimbing, S.C. (Universitas Sam Ratulangi, 2021)
SENSORICAL QUALITY AND PHYSICAL PROPERTIES OF CHICKEN NUGGETS WHICH IS ADDED PURPLE ROAD UBI FLOUR (Ipomoea batatas L). This study aims to determine the benefits of using purple sweet potato flour (Ipomoea batatas L) on the sensory quality and physical properties of chicken nuggets. The research was carried out in 3 stages, namely (1) making purple sweet potato flour, (2) making chicken nugets with the addition of purple sweet potato flour, (3) testing chicken nuggets including sensory quality testing using 35 untrained panelists to measure the level of acceptance of aroma, color, texture and taste, physical properties test to determine water binding power and cooking losses. This research was conducted experimentally using a completely randomized design with 4 additional treatments of purple sweet potato flour, namely P1 = 10 g, P2 = 20 g, P3 = 30 g and P4 = 40 g, each treatment was repeated as many as 35 (panelists) for the test. sensory quality and 5 replications for physical characteristics test. Data from the observation of sensory quality test, physical properties were tabulated and analyzed by analysis of variance (Ansira) and if there were significant differences between treatments, it was continued with Duncan's multiple test (DMRT). The results of the research with analysis of variance showed that the addition of 10, 20, 30 and 40 grams of purple sweet potato had a very significant effect (P <0.01) on color, texture, water-binding capacity and cooking loss but had no significant effect. (P> 0.05) on aroma and taste. The results of Duncan's multiple further test showed that the P4 treatment of 40 g of purple sweet potato gave the best results on color, texture, water binding power and cooking loss. Based on the results and discussion, it can be concluded that the addition of 40 g of purple sweet potato flour in the manufacture of chicken nuggets provides good sensory quality and physical properties.Keywords: Chicken nuggets, purple sweet potato flour, sensory quality, physical properties